Inflation expectations - Sinclair, P. J. N. (London ; New York : Routledge, 2010)
This is a collection of papers from world experts (Roy Batchelor, Richard Curtin and Staffan Linden) on inflation expectations; likely inflation developments; the spread of inflation targeting, invented in New Zealand over 15 years ago, but now encompassing many important economies including Brazil, Canada, Israel and Great Britain. Not left out is the European Central Bank, the Bank of Japan and the United States Federal Bank which were considering or implementing inflation targeting.
Includes bibliographical references and index.
lje 30/04/13
Loan
Keywords: Inflation (Finance); Rational expectations (Economic theory)